CSR, Good Corporate Governance, Corporate Value: Moderation of Financial Performance - Wati, Yenny; Irman, Mimelientesa; Suharti; Suyono; Renaldo, Nicholas (Politeknik Caltex Riau, 2023)
This research aimed to look into the effects of corporate social responsibility and good corporate governance on corporate value. In this study, which looked at three independent variables on corporate value, researchers used financial performance as a moderating variable. Secondary data sources for this study have been gathered from the IDX (Indonesian Stock Exchange) for the period 2018-2022, with manufacturing enterprises serving as the sample. This research was carried out utilizing WarpPLS, a data analysis method that employs partial least squares. Corporate social responsibility and good corporate governance boost the value of a corporation. The influence of corporate social responsibility and good corporate governance on corporate value can be moderated by financial performance. Corporations may enhance the way they perform to provide better value and raise stock returns. The study's findings can be used by investors to make informed investment decisions. Corporate social responsibility and good corporate governance policies are one approach for the company to provide a favorable signal to stakeholders and the market about its future survival prospects. Keywords: corporate value, corporate social responsibility, good corporate governance, financial performance